Knowledge Level Analysis of Community stigma on ODP, PDP and COVID 19 patients through attitude in Kediri District - Astutik, Wahyu Sri; Nugraheni, Reny (STRADA : Jurnal Ilmiah Kesehatan, 2020)
One of the problems arising from Covid 19 is the occurrence of stigma in ODP, PDP, Covid 19 Patients, even in health professionals who can cause the failure of the Covid 19 prevention program. If not immediately find the cause of this stigma, and then the stunting prevention program will not run optimally. The purpose of the research is to determine the effect of knowledge on attitude, to know the effect of knowledge on stigma, to determine the effect of attitude on stigma and to determine the effect of knowledge on stigma through attitude. The population in this study was the people of Kediri Regency, and the sample in this study was random sampling and received a sample of 150 people. The results showed that knowledge influences attitude, knowledge influences stigma, attitude influences stigma and knowledge influences stigma through attitude